Experimentally elevated testosterone shortens telomeres across years in a free‐living songbird. Issue 23 (9th February 2021) - Heidinger, Britt J.; Slowinski, Samuel P.; Sirman, Aubrey E.; Kittilson, Jeffrey; Gerlach, Nicole M.; Ketterson, Ellen D.
Abstract: Reproductive investment often comes at a cost to longevity, but the mechanisms that underlie these long‐term effects are not well understood. In male vertebrates, elevated testosterone has been shown to increase reproductive success, but simultaneously to decrease survival. One factor that may contribute to or serve as a biomarker of these long‐term effects of testosterone on longevity is telomeres, which are often positively related to lifespan and have been shown to shorten in response to reproduction. In this longitudinal study, we measured the effects of experimentally elevated testosterone on telomere shortening in free‐living, male dark‐eyed juncos ( Junco hyemalis carolinensis ), a system in which the experimental elevation of testosterone has previously been shown to increase reproductive success and reduce survival. We found a small, significant effect of testosterone treatment on telomeres, with testosterone‐treated males exhibiting significantly greater telomere shortening with age than controls. These results are consistent with the hypothesis that increased telomere shortening may be a long‐term cost of elevated testosterone exposure. As both testosterone and telomeres are conserved physiological mechanisms, our results suggest that their interaction may apply broadly to the long‐term costs of reproduction in male vertebrates.